Incorporating patient-reported outcome measures into routine paediatric pharmacovigilance: opportunities for safety monitoring with practical use scenarios from paediatric oncology - Teodoro, Pedro; Fernandes, Ricardo M.; Ribeiro, Inês; Ferreira-da-Silva, Renato (Frontiers in Pharmacology, 2026)
BackgroundTraditional pharmacovigilance systems often fail to capture children’s experiences of adverse events (AEs), particularly subjective symptoms that affect daily functioning and quality of life. Patient-Reported Outcome Measures (PROMs) offer a complementary perspective by enabling direct input from children or their caregivers on treatment-related outcomes.ObjectivesTo examine how PROMs can be integrated into routine paediatric pharmacovigilance and to propose practical use scenarios that illustrate their potential applications.MethodsWe conducted a targeted narrative review using MEDLINE (via PubMed), Scopus, and Web of Science, complemented by manual searches of regulatory guidance and reference lists. Studies were included if they addressed the use of PROMs in paediatric contexts relevant to pharmacovigilance. Extracted data were synthesised across domains, including measurement properties, regulatory uptake, and potential for safety monitoring. The search was carried out in June 2025.ResultsPROMs have demonstrated strong validity, feasibility, and relevance for detecting symptomatic AEs and monitoring health-related quality of life in paediatric populations. Instruments such as PROMIS Paediatric and other condition-specific tools have been successfully used across clinical, regulatory, and research settings. PROMs enhance the detection and characterisation of AEs by capturing dimensions not readily assessed through traditional spontaneous reporting. Building on these findings, we present five practical use scenarios that exemplify how the Ped-PRO-CTCAE can be adapted for real-world safety monitoring in pharmacovigilance workflows, including spontaneous reporting, EHR-based monitoring, pharmacy-based follow-up, and medication rechallenge.ConclusionPROMs offer a structured, patient-centred approach to paediatric pharmacovigilance, enhancing post-marketing safety monitoring through systematic symptom reporting.